A sociocultural model of play-based pedagogy for teaching mathematics in diverse Grade R classrooms in South Africa - Muthivhi, Azwihangwisi (University of Pretoria, 2025)
Thesis (PhD (Early Childhood Education))--University of Pretoria, 2024.